(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to clarify the nature of the relationship between compassionate leadership and the continuous improvement procedures adopted by the organization under study, as compassionate leadership refers to focusing on relationships through careful listening to others, understanding them, empathizing with them and supporting them, and enabling followers to feel appreciated, respected and cared for, so that they can reach their potential. And to do their work as best as possible, as Iraqi organizations face a problem in their inability to spread continuous improvement practices in their business environment. Therefore, the current research attempts to bridge this gap by providing compassionate leadership as a tool to spread continuous improvement in the organization’s environment. In order to achieve the research objectives, the researchers adopted the descriptive approach. Analytical, which is based on taking the opinions of some employees at Al-Mustaqbal university, which is a sample representative of the university as a whole. By distributing (125) questionnaires to the employees of the National University of the Future, (112) questionnaires were retrieved, of which (100) were suitable for statistical analysis. The research reached To a set of conclusions, the most prominent of which is that careful leadership has a positive impact on achieving continuous improvement, while the research presented a set of recommendations, the most important of which is that organizations working in the field of higher education should adopt careful leadership practices because they contribute to raising employee morale, creating team spirit, and stimulating their positive behaviors.